2020
DOI: 10.1186/s12879-020-05129-w
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcal antigenemia and its predictors among HIV infected patients in resource limited settings: a systematic review

Abstract: Background: Cryptococcosis is an opportunistic fungal infection that primarily affects people with advanced HIV/ AIDS and is an important cause of morbidity and mortality around the globe. By far the most common presentation of the disease is cryptococcal meningitis (CM), which leads to an estimated 15-20% of all HIV related deaths worldwide, 75% of which are in sub-Saharan Africa. However, to the best of our knowledge there is quite limited reviewed data on the epidemiology of cryptococcal antigenemia in a la… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 51 publications
0
7
0
3
Order By: Relevance
“…This implies that the overall CM prevalence among PLWH in the study could have been much lower or even closer to our African estimate. A systematic review by Derbie et al found the prevalence of cryptococcal antigenemia to be 8% (95% CI 6–10) which was almost double our prevalence for CM which was logical since not all cases of cryptococcal antigenemia result in invasive cryptococcal disease ( 55 ). Although cryptococcal antigenemia is not equivalent to a diagnosis of CM, it has been thought of as an important proxy measure for CM in PLWH ( 60 ).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…This implies that the overall CM prevalence among PLWH in the study could have been much lower or even closer to our African estimate. A systematic review by Derbie et al found the prevalence of cryptococcal antigenemia to be 8% (95% CI 6–10) which was almost double our prevalence for CM which was logical since not all cases of cryptococcal antigenemia result in invasive cryptococcal disease ( 55 ). Although cryptococcal antigenemia is not equivalent to a diagnosis of CM, it has been thought of as an important proxy measure for CM in PLWH ( 60 ).…”
Section: Discussionmentioning
confidence: 72%
“…However, culture has drawbacks which include being more expensive and delaying diagnosis by 3–7 days ( 54 ). The use of serum cryptococcal antigen (CRAG) testing is indicated as a screening method for likely CM in advanced HIV and is only used to commence prophylactic therapy among CRAG-positive individuals ( 14 , 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…in his pediatric cohort population study carried out in China in 2017, found that 19 children (35.8%) had history of exposure to poultry including 11 children exposed to pigeons and 8 exposed to chickens [ 14 ]. Numerous other studies have suggested that Cryptococcus neoformans is found worldwide in association with the feces of certain birds such as pigeons [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in Nigeria [ 19 ], Ghana [ 20 ], Benin [ 21 ], Burkina Faso [ 21 ], Cote d'Ivoire [ 21 ], Mali [ 21 ], Senegal [ 21 ], and Sierra Leone [ 22 ] have similarly reported an AIDS-related death rate of around 30% among hospitalized patients, as in our study. Opportunistic infections are reported in Africa as the leading cause of hospitalization for AIDS-related deaths [ 12 , 23 , 24 ]. Similar findings were observed in our series.…”
Section: Discussionmentioning
confidence: 99%